Baicalin Prevents Myocardial Ischemia/Reperfusion Injury Through Inhibiting ACSL4 Mediated Ferroptosis - Fan, Zhenyu; Cai, Liangliang; Wang, Shengnan; Wang, Jing; Chen, Bohua (Frontiers in Pharmacology, 2021)
Baicalin is a natural flavonoid glycoside that confers protection against myocardial ischemia/reperfusion (I/R) injury. However, its mechanism has not been fully understood. This study focused on elucidating the role of ferroptosis in Baicalin-generated protective effects on myocardial ischemia/reperfusion (I/R) injury by using myocardial I/R rats model and oxygen-glucose deprivation/reoxygenation (OGD/R) H9c2 cells. Our results showed Baicalin improved myocardial I/R challenge induced ST-segment elevation, infarct area and pathological changes, and prevented OGD/R-triggered cell viability loss. In addition, reduced ROS, MDA and Fe2+ production, enhanced SOD activity and restored protein levels of ACSL4, transferrin receptor protein 1 (TfR1), GPX4 and ferritin heavy chain 1 (FTH1) were observed in vivo and in vitro after Baicalin intervention. However, ACSL4 overexpression compromised Baicalin-generated protective effect in H9c2 cells. Taken together, our findings suggest that Baicalin prevented against myocardial ischemia/reperfusion injury via suppressing ACSL4 controlled ferroptosis. This study provides a novel target for the prevention of myocardial ischemia/reperfusion injury.